Komunikasi Visual Iklan Layanan Masyarakat Dampak Buruk Kesehatan Akibat Karhutla Di Kota Palembang - Dery Dzawil Qodry; Mukhsin Patriansah (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Forest and Land Fires (KARHUTLA) often occur almost every year and have become a regular source of ecological disasters such as causing unhealthy air pollution for the community. Palembang City is an area that often experiences smog every year. The negative impacts resulting from forest and land fires are very detrimental to several parties, generally people will have their activities and health disrupted such as disruption to flight schedules, schooling and community activities will be disrupted such as lack of visibility and danger for traffic travel. building the value of public awareness and alertness regarding the negative impacts of KARHUTLA on health, it is necessary to